(untitled) (Annals of Medical Research, 2026)
Aim: To investigate the possible effects of harmful Tartrazine and protective Thymoquinone on brain tissue in Wistar albino rats. Materials and Methods: Thirty-two rats were divided into 4 groups: Control (n=8), Tartrazine (n=8), Thymoquinone (n=8), and a combination of Tartrazine and Thymoquinone (n=8). Tartrazine and Thymoquinone were administered orally via gavage for 3 weeks, and the brain tissues were collected after the 3-week period. Oxidant-antioxidant parameters such as malondialdehyde (MDA), glutathione (GSH), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), catalase (CAT) were examined. Results: There were differences between the Tartrazine and all other groups. Tartrazine administration led to a significant increase in MDA and SOD enzymes activity levels in brain tissue. It also caused a significant decrease in reduced GSH, GSH-Px and CAT activities. Thymoquinone administration caused an increase in GSH, GSH-Px enzymes activity, and CAT enzymes activity levels compared to all other groups. Conclusion: This study examined the effects of tartrazine and thymoquinone on brain tissue found that tartrazine has neurotoxic effects. We believe that the neurotoxicity caused by tartrazine results from oxidative stress, increased oxidant capacity, and decreased antioxidant capacity. Thymoquinone may serve as a neuroprotective agent because it significantly increased antioxidant capacity.